Scanning two-grating free electron Mach-Zehnder interferometer - Cameron W. Johnson; Amy E. Turner; Benjamin J. McMorran (Physical Review Research, 2021)
We demonstrate a two-grating free electron Mach-Zehnder interferometer constructed in a transmission electron microscope. A symmetric binary phase grating and a condenser lens system form two spatially separated, focused probes at the sample which can be scanned while maintaining alignment. The two paths interfere at a second grating, creating constructive or destructive interference in the output beams. This interferometer has many notable features: positionable probe beams, large path separations relative to beam width, continuously tunable relative phase between paths, and real-time phase information. Here we use the electron interferometer to measure the relative phase shifts imparted to the electron probes by electrostatic potentials as well as a demonstration of quantitative nanoscale phase imaging of a polystyrene latex nanoparticle.